PEMBUATAN APLIKASI PEMBANTU PEMANDU WISATA BERBASIS ANDROID - Billy Samuel Fernanda; Lisana Lisana; Andre Andre (CALYPTRA, 2018)
“Aplikasi Pembantu Pemandu Wisata” is an application that created to help the work of tour guides in explaining the travel guides. Refer to their difficulty of giving an explanation, especially in crowded conditions, is the main concept of this application. With voice broadcasting feature that is captured from a cell phone guides and sent to all mobile phone participants can relieve guide jobs. The sound will be sent through a wifi connection-direct connected with the guide. In addition to the voice broadcasting feature, also a feature to send notification that serves to remind the participants if the time has come to gather. User interface implemented on the concept of one-handed operation that allows the user to operate easily with one hand. After implementing and testing with survey and observation, the result showed that the tour guide helper application is made to facilitate the tour guides and tour participants.